A Conceptual Model of Protective Factors Within Aboriginal and Torres Strait Islander Culture That Build Strength. (October 2021) - Hunter, Sue-Anne; Skouteris, Helen; Morris, Heather
The Aboriginal and Torres Strait Islander Australian population have endured immense hardship since the colonization of Australia characterized by the loss of lands, language, leadership, and family that contributes to the health and social inequities experienced today. Culture plays a significant role in shaping the health and wellbeing of all Aboriginal and Torres Strait Islander peoples, however the processes and mechanisms of cultural connection, how it builds strength and offers protection in times of hardship is less clear. This scoping review used the voice of Aboriginal and Torres Strait Islander Australians from qualitative research papers to hear what cultural factors are protective and the ways they offer this. Quantitative research papers were then explored to understand if connection to culture lead to better health or social outcomes. Four aspects of culture were integrated into a conceptual model—cultural activities, country, connection, and identity. The eight quantitative papers assessed connection to culture poorly making it difficult to definitively determine if a strong cultural connection leads to better outcomes. Practice implications and future directions led by this conceptual model are provided.